Effect of Methanol Induction and Incubation Time on Expression of Human Erythropoietin in Methylotropic Yeast Pichia Pastoris - Santoso, Adi; Herawati, Neng; Rubiana, Yana (Makara Journal of Technology, 2012)
Erythropoietin (EPO) is a glycoprotein hormone consists of 165 amino acids and has molecular mass of 30,400 Daltons. The large quantities of these hormone required to satisfy clinical demand are currently met by recombinant expression in mammalian cell, namely chinese hamster ovary (CHO). Pichia pastoris has become popular yeast based protein production systems to substitute mammalian expression systems. P. pastoris is capable to use methanol as sole carbon and energy source. In this study, recombinant human EPO (rhEPO) protein obtained by expressing the hEPO gene in methylotropic yeast P. pastoris, strain X33. The present work was carried out to study the optimal methanol concentration for induction and the incubation time to obtain rhEPO protein. To perform this study, the transformed P. pastoris was induced with various concentrations of methanol (0%, 0.5%, 1%, 2.5%, 5%, 10%, and 20%) and incubation times (0 hours, 24 hours, 48 hours, 72 hours, 96 hours, 120 hours, and 144 hours). The results demonstrate that the highest protein expression level occurred at concentration of 2.5% methanol induction, while the optimal incubation time was at 48 hrs.